The Effect of Growth Mindset on Work Readiness: The Mediating Role of Occupational Health and Safety (OHS) Competence and the Contribution of Seafaring Experience - Adhi Pratistha Silen (Jurnal Kebijakan Sosial Ekonomi Kelautan dan Perikanan, 2026)
The urgency of strengthening work safety mindset and occupational health and safety (OHS) competence has become a policy priority for Indonesia’s maritime human resource development in facing global competition and STCW (Standards of Training, Certification and Watchkeeping for Seafarers) requirements. This study aims to analyze the effects of growth mindset and OHS competence on work readiness, as well as the role of seafaring experience, as an empirical basis for formulating holistic maritime HR development policies. The research employed a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) with 243 upgrading trainees at Politeknik Ilmu Pelayaran Semarang, measuring growth mindset, work readiness, OHS competence, and seafaring experience constructs. Results show that growth mindset positively and significantly affects work readiness (β=0.225; t=3.659; p<0.001) and OHS competence (β=0.406; t=4.395; p<0.001). OHS competence strongly influences work readiness (β=0.547; t=6.600; p<0.001). Seafaring experience significantly contributes to growth mindset (β=0.542; t=7.255; p<0.001), work readiness (β=0.194; t=3.145; p=0.002), and OHS competence (β=0.528; t=5.881; p<0.001). Mediation analysis confirms the significant role of OHS in the growth mindset→work readiness pathway (indirect effect=0.222; 95% CI [0.131; 0.361]). Policy implications include strategic recommendations: (1) integration of growth mindset modules in national maritime training curricula; (2) strengthening OHS training portion and quality to minimum 20-25% of total training hours; (3) implementation of Recognition of Prior Learning (RPL) systems for seafaring experience validation; (4) development of evidence-based holistic competency assessment standards. This research contributes to transforming Indonesia’s maritime HR development policy towards excellence in maritime human capital supporting the world maritime axis vision.